Perkembangan Kepribadian dan Emosi Gaya Pengasuhan Coraline dalam Novel Coraline: Analisa Kritik BaruCoraline - Giawa, Maria Hanny Paskaline (Linguistika Kultura, 2024)
Parenting style is something that is close to us in our daily lives, and it is because of this that we have become the person we are today. A parenting style from parents to their children can affect the development of the child’s personality and emotions in their process towards adulthood. The purpose of this study is to see how Coraline’s personality is affected by the different parenting styles between real parents and ‘other parents’. This study uses New Criticism as an approach to analyze the characterization and plot of the story and therefore examines how Coraline’s personality is affected by the different parenting styles between the real parents and the 'other parents'. Therefore, the method used in this study is descriptive-qualitative. The results of this study found that the personality of Coraline was formed because of parenting styles from her parents and Coraline's emotions change depending on what her parents gave.